Sporting event attributes and behavioural intention: mediating effect of destination image / Dhiya Hikmahana Abdul Razak and Aslinda Mohd Shahril - Abdul Razak, Dhiya Hikmahana; Mohd Shahril, Aslinda (Faculty of Hotel Management and Tourism, Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2017)
This research examines the relationship between sports tourism event attributes (access quality, accommodation quality, and venue quality) and international participants revisit intention to join another sporting event. Furthermore, this study attempts to explore the influence of destination image as a mediator between the relationship of sports tourism event attributes and behavioral intention. It briefly argued that sports event can add the attractiveness of the destination. This research function is exploratory studies which determine the necessary influence of attributes in the sports tourism event to define the concept. Statistical analysis was employed which is reliability test, descriptive analysis by using the mean score and multiple regressions approach which is to explore the relationship between dependent variable and independent variable. For this study, questionnaires were distributed to international participants who joined running event conducted at Putrajaya. The findings from this study presented that, the main hypothesis and three sub-hypotheses were not fully supported. By taking into these considerations, for the future research, it might need to take into though consideration to use a qualitative approach to explore more crucial information.